Ryzyko długowieczności dla portfela ubezpieczeń na życie i zakładów emerytalnych - Papież, Monika (The Longevity Risk for the Portfolio of the Life Insurance and Pension Plans, 2008)
The paper presents the analysis of the influence of ageing process of the population on the assessment of the products of insurance companies regarding living benefits. In the assessment and management of living benefits two fundamental risk sources play a fundamental role: the investment risk and the demographic risk. The demographic risk is divided into components: the insurance risk and the longevity risk. The longevity risk is particularly important; it derives from improvements in mortality trend which determine systematic deviations of the number of deaths from its expected values. The article presents the influence of growth of number of policies of life annuities in portfolio on size of insurance and longevity risk. This analysis shows that the growth of number of policies causes reduction in insurance risk and the increase of longevity risk. Hence appropriate policy is important for longevity risk management. So, the paper also presents LifeMetrics - a toolkit for measuring and managing longevity risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 327-335